Imipenem/cilastatin encapsulation in UIO-66-NH2 carrier as a new strategy for combating imipenem-resistant Pseudomonas aeruginosa isolates - Shakila Baei Lashaki; Pooria Moulavi; Fatemeh Ashrafi; Aram Sharifi; Sepideh Asadi (Journal of Global Antimicrobial Resistance)
Background: This study aims to investigate the effectiveness of UIO-66-NH2, a metal-organic framework, as a carrier for imipenem/cilastatin (Imp/Cil) in overcoming resistance in clinical isolates of imipenem-resistant Pseudomonas aeruginosa. Methods: The UIO-66-NH2-Imp/Cil formulations were synthesized and characterized using dynamic light scattering, scanning electron microscopy, and transmission electron microscopy. Drug entrapment efficiency of UIO-66-NH2-Imp/Cil, and Imp/Cil release rates were determined. The stability of formulations was assessed at room temperature and refrigeration for two months. The antibacterial, anti-biofilm, and anti-virulence activities of formulations were investigated against imipenem-resistant P. aeruginosa isolates. Results: The UIO-66-NH2-Imp/Cil formulation showed an average particle size of 212.3 ± 7.3 nm, a polydispersity index of 0.142 ± 0.010, and an entrapment efficiency (EE%) of 74.19% ± 1.12%. Drug release from the formulation followed a Korsmeyer-Peppas kinetic model, with 52% of the drug released over 72 h. Antibacterial testing indicated a significant decrease in minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for the UIO-66-NH2-Imp/Cil formulation compared to free Imp/Cil, demonstrating enhanced antibacterial activity. Furthermore, the anti-biofilm and anti-virulence activity of UIO-66-NH2-Imp/Cil was confirmed by the reduction of bacterial haemolysis activity, minimal pyocyanin, EPS (extracellular polymeric substance) production, and lower metabolic activity of pathogens. Also, UIO-66-NH2-Imp/Cil causes significant reduction in the expression of lasA, lasB and, rhlA genes, which resulted in the inhibition of quorum-sensing system activity. Conclusions: These findings indicate that UIO-66-NH2-Imp/Cil nanocarriers offer a promising new approach against multidrug-resistant Gram-negative pathogens, providing insights into potential mechanisms of antimicrobial action.